Nursing management of ventilation in patients with SARS-CoV-2 infection (Scenario® - Il Nursing nella sopravvivenza, 2021)
Patients with COVID-19 interstitial pneumonia often require non-invasive ventilation. The aim of the study is to retrospectively evaluate the effectiveness of a nursing intervention with a team leader/case manager with expertise in pulmonology/ventilation compared with standard care in facilitating return to room air breathing and the use of non-invasive ventilatory support in a sample of patients with COVID-19 pneumonia admitted to the High Dependency Unit (HDU).